The Relationship Between Motivation and Organizational Culture on The Performance Employees Department of Tourism Kupang City Mediated by Job Satisfaction - David Manafe; Rosadalima Tisu; Maria Augustin Lopes Amaral (Enrichment : Journal of Management, 2022)
The purpose of this study to analyze the effect of work motivation and organizational culture on employee performance moderated by job satisfaction at the Department of Tourism of Kupang city. This type of research is quantitative survey research. The population and sample in this study amounted to 52 people. Collecting data through interviews, questionnaires, and documentation. This research uses quantitative survey research. The results of research show that work motivation does not have a significant effect on employee performance, organizational culture does not have a significant effect on employee performance, job satisfaction has a significant effect on employee performance, work motivation has no significant effect on job satisfaction and organizational culture has a significant effect on job satisfaction. The results of the mediation test show that job satisfaction cannot mediate work motivation on employee performance and job satisfaction can mediate organizational culture on employee performance.